2016
DOI: 10.1051/0004-6361/201527423
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength analysis for interferometric (sub-)mm observations of protoplanetary disks

Abstract: Context. The growth of dust grains from sub-µm to mm and cm sizes is the first step towards the formation of planetesimals. Theoretical models of grain growth predict that dust properties change as a function of disk radius, mass, age, and other physical conditions. High angular resolution observations at several (sub-)mm wavelengths constitute the ideal tool with which to directly probe the bulk of dust grains and to investigate the radial distribution of their properties. Aims. We lay down the methodology fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
215
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(236 citation statements)
references
References 70 publications
(139 reference statements)
21
215
0
Order By: Relevance
“…The β(r) profiles are qualitatively consistent with the results of similar analyses performed in other classical smooth disks (Guilloteau et al 2011;Banzatti et al 2011;Pérez et al 2012Pérez et al , 2015Trotta et al 2013;Menu et al 2014;Tazzari et al 2016), with a significant variation of β throughout the disk (∆β > 1), indicating a maximum grain size a max decreasing with the distance from the star. The ALMA and VLA data provide for the first time the combination of signal-to-noise ratio, angular resolution and image fidelity to successfully perform an analysis in the image plane.…”
Section: β(R) Profiles and Grain Growthsupporting
confidence: 86%
See 3 more Smart Citations
“…The β(r) profiles are qualitatively consistent with the results of similar analyses performed in other classical smooth disks (Guilloteau et al 2011;Banzatti et al 2011;Pérez et al 2012Pérez et al , 2015Trotta et al 2013;Menu et al 2014;Tazzari et al 2016), with a significant variation of β throughout the disk (∆β > 1), indicating a maximum grain size a max decreasing with the distance from the star. The ALMA and VLA data provide for the first time the combination of signal-to-noise ratio, angular resolution and image fidelity to successfully perform an analysis in the image plane.…”
Section: β(R) Profiles and Grain Growthsupporting
confidence: 86%
“…3.4 we have shown that the surface brightness radial profile for the continuum emission at 850 µm is compatible with having an excess peaked around 110 AU, with deconvolved FWHM ≤ 40 AU. To assess the robustness of this result, we performed a direct fit of the interferometric data (i.e., the visibilities) using the fitting scheme described by Tazzari et al (2016) to which we refer for the analysis details. To estimate the disk thermal emission at 850 µm, we used a classical two layer disk model (Chiang & Goldreich 1997) with refinements by (Dullemond et al 2001) and a reduced disk flaring that adequately describes the observed far-infrared flux (from Tilling et al 2012).…”
Section: Modeling Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the radial profile ofˇroughly corresponds to theǎ s a function of different grain sizes. There have been some observational constraints on the radial profile by using interferometric observations at radio wavelengths, which shows thatˇis small inside the disk and large outside the disk (e.g., Isella et al 2010;Guilloteau et al 2011;Pérez et al 2012Pérez et al , 2015Tazzari et al 2016). …”
Section: Opacity Evolutionmentioning
confidence: 99%